IJCM_202A: Catastrophic health expenditure (CHE) due to diabetes mellitus among urban slum population of Agra city- An Observational study - Prathyusha Lingareddy; Agrawal Renu; Singh Geetu; Kumar Sarvesh (Wolters Kluwer Medknow Publications, 2024)
Background: People with diabetes need extensive self-management support, medications, regular screening for and treatment of possible complications and comorbidities, all of which can increase out-of-pocket (OOP) costs in patients and their families. There is a very strong correlation between the level of OOPs and an indicator that is used to monitor how well a health system is performing in terms of financial protection namely, incidence of catastrophic health expenditure. Objectives: 1. To assess the catastrophic health expenditure on treatment of diabetes mellitus and its complications in the study population. 2. To find out the association of CHE with sociodemographic profile, diabetic profile, and treatment compliance among the study population. Methodology: After applying the inclusion criteria 360 known diabetics were included from the four randomly selected slum areas of Agra city. A cross- sectional study through face-to-face interview using predesigned, pretested, and semi-structured questionnaire was conducted from September 2020 to March 2022. Data was entered on MS excel and appropriate statistical analysis was done. Results: Males and females were 59% and 41% respectively. Nearly 66% participants were of age group 35-60 years, 28% were illiterates, 54% were unemployed & 44% belong to upper lower socioeconomic class. Almost 96% were having type 2 diabetes, 74% were on oral hypoglycaemic agents and 70% were compliant to treatment. Monthly median direct out-of-pocket expenses were INR 1500 and indirect expenses were INR 505. Type of diabetes, and treatment regimen were the factors found to be associated with Catastrophic health expenditure. Conclusion: A significant proportion of 39.4% of the study participants were found to have catastrophic health expenditure.